Genetic variability, heritability and genetic advance studies in topcross and three-way cross maize (Zea mays L) hybrids - Sesay, S.; Ojo, D.; Ariyo, O.J.; Meseka, S. (2016)
Understanding the genetic variability, heritability and genetic advance of traits in any plant population is an important pre-requisite for selection program. This study was designed to assess the magnitude of genetic variability, heritability and genetic advance of traits in top-cross and three-way cross maize (Zea mays L) hybrids evaluated at three locations in South-Western Nigeria. The trial consisted of ten genotypes each of top-cross and three-way cross hybrids arranged in randomized complete block design with three replications. Data on grain yield and other desirable traits across the three locations were used to estimate the genetic variability parameters, heritability and genetic advance (GA). Highly significant (P ≤ 0.01) differences were detected within each hybrid class for all the traits. Traits evaluated in this study exhibited different levels of variability, heritability and genetic advance between the two hybrid classes. Low to moderate phenotypic coefficient of variation (PCV) and genotypic coefficient of variation (GCV) were recorded. Also, low to very high heritability and low to high GA values were recorded for all the traits measured in the top-cross hybrids, whereas the three-way cross hybrids exhibited low to moderately high heritability estimates and low to moderate GA values. Grain yield and field weight showed moderate GCV, moderately high heritability and high GA values in top-cross hybrids. These characters exhibited moderate GCV but low heritability and GA values in three-way hybrids. More characters in top-cross hybrids revealed sufficient amount of variability than in three-way cross hybrids, thus offer scope for genetic improvement through selection.